A Near Miss and Salvage Management of Aortoesophageal Fistula Secondary to Cell Battery Ingestion. Issue 1 (January 2020) - Bartkevics, Maris; Stankovic, Zoran; Schibli, Susanne; Fluri, Simon; Berger, Steffen; Schmidli, Juerg; Kadner, Alexander
We report a case of an infant surviving aortoesophageal fistula secondary to lithium cell battery ingestion. In the setting of a delayed vascular complication, computed tomography and magnetic resonance imaging are essential to establishing the correct diagnosis and surgical management. Management of children after battery ingestion must be guided by a high index of clinical suspicion.